+0  
 
0
149
1
avatar

(d-1)/5 = (d-3)/3

 

Solve the equation 

Guest Apr 6, 2017
Sort: 

1+0 Answers

 #1
avatar+5541 
+3

\(\frac{d-1}{5}=\frac{d-3}{3}\)

 

Cross-multiply.

\((3)(d-1)=(5)(d-3)\)

 

Distribute.

\(3d-3=5d-15\)

 

Subtract 3d from both sides.

\(-3=5d-3d-15\)

 

Add 15 to both sides.

\(-3+15=5d-3d \\~\\ 12=2d\)

 

Divide both sides by 2.

\(\frac{12}{2}=d \\~\\ 6=d\)

hectictar  Apr 6, 2017

22 Online Users

avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details